(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
The song Bayar Bayar Bayar by the punk band Sukatani sparked controversy in Indonesia, showing how punk music has become a tool of social criticism of economic policies and structural injustices. This issue is important in the broader discourse on cultural censorship, freedom of expression, and the role of institutions in responding to social criticism through music. This research aims to analyze the meaning of the song’s lyrics, public and media reactions, and institutional responses to them. Using a qualitative method with critical discourse analysis, this study examines media texts, audiovisual recordings, and interviews with academics. The results of the analysis show that punk music remains a form of resistance to state hegemony, despite facing censorship and silencing. Thus, the repressive response to music with social criticism strengthens the song’s appeal as a symbol of resistance. This study emphasizes the need for more inclusive cultural policies, as well as more open dialogue between artists and institutions to accommodate freedom of expression in public spaces.